A Survey on Smart Analytics: Method, Tools, and Open Research Issues - Nova Nurviana (APIC, 2020)
Smart analytic nowadays was very popular because today big data is booming. Back several years ago, people were fascinating with statictics which surveys or cencus become a gun for describing or forecasting some issues as of decision making or planning. By migrating to big data, smart analytic is very needed to filter which data is useful and producing some worthy information.